Integrative research: Current trends and considerations for biomarker discovery and precision medicine - Jessica Grace Cockburn; Vanitha Mariappan; Mun Fai Loke; Anis Rageh Al-Maleki; Barathan Muttiah; Kumutha Malar Vellasamy; Jamuna Vadivelu (The Microbe)
The development of molecular biology, from the discovery of DNA's double-helix to current genomic tools, has revolutionized biomedical science. Integrative research, with the inclusion of genomic, proteomic, and clinical data, plays a critical role in biomarker identification and precision medicine. This review describes how integrative approaches enable better disease classification, such as breast cancer, for targeted therapy and improved patient care. Some of the most important technology advancements—next-generation sequencing, multi-omics integration, artificial intelligence, and single-cell omics—have sped up this field. With the use of directed and undirected biomarker discovery platforms, researchers can identify specific molecular markers or explore novel candidates in different biological layers. These methods have enabled the exploration of complex diseases, from COVID-19 to chronic conditions. Nevertheless, data complexity, computational limitations, and ethical concerns in personalized diagnosis persist. To overcome them, is the key to crossing the gap from computational knowledge into medical application. Enhancing the diagnostics of diseases, improving therapeutics' precision, and facilitating patient therapy are the general objectives of integrated investigations. By advancing the most technology available in computing and molecules, researchers are going towards more precision-guided and effective medicine.